Incidence of R factors in coliform, fecal coliform, and Salmonella populations of the Red River in Canada. - Bell, J B (1980)
Coliforms, fecal coliforms, and Salmonella were isolated from the Red River, Manitoba, Canada, and identified. These organisms were then examined for resistance to 12 antibiotics. Some fecal coliforms were resistant to all 12 antibiotics, and 18% of the Salmonella isolates were resistant to one or more antibiotics. A total of 52.9% of the fecal coliforms resistant to three or more antibiotics were able to transfer single or multiple resistance (R) determinants to the Salmonella recipient, and 40.7% could transfer R determinants to the Escherichia coli recipient. Of the resistant Salmonella, 57% transferred one or two determinants to the Salmonella recipient, and 39% transferred one or two determinants to the E. coli recipient. It was calculated that populations of fecal coliforms containing R factors were as high as 1,400 per 100 ml and that an accidental intake of a few milliliters of water could lead to transient or permanent colonization of the digestive tract. Consideration of data on bacteria with R factors should be made in future water quality deliberations and in discharge regulations.